Halogenases for biosynthetic pathway engineering: Toward new routes to naturals and non-naturals. Issue 3 (3rd July 2022) - Menon, Binuraj R. K.; Richmond, Daniel; Menon, Navya
ABSTRACT: Nature's repertoire of bio-halogenase enzymes is intriguing with halogenases from various natural product biosynthetic clusters that carry out site and region-specific halogenation of diverse bioactive precursors and molecules. Currently, we have a comprehensive catalogue of cryptic and non-cryptic halogenases that act on simple to complex aliphatic and aromatic molecular scaffolds. This will open up further synthetic and biosynthetic opportunities for C-H activation, ring formation and functionalization of different molecular structures. In fact, halogenases were exploited over the years for these potential applications, to replace traditional chemical halogenation chemistries toward creating economical and environmentally benign methodologies and also for biosynthetic pathways. This review will discuss our advances in utilizing bio-halogenases to generate both in vivo and in vitro biosynthetic pathways; summarizing all naturals and non-naturals that are synthesized with a direct bio-halogenase incorporation.